THE EFFECTS OF CLAM EXERCISE WITH VISUAL FEEDBACK ON THE HIP MUSCLE STRENGTH OF PATIENTS WITH CHRONIC STROKE - Park, Jin (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to compare the strength of patients with chronic stroke following either clam exercise with visual feedback (feedback group) or clam exercise without visual feedback (control group).Fourteen subjects with chronic stroke were recruited from rehabilitation hospital. The subjects were divided into two groups: a feedback group (7 subjects) and a control group (7 subjects). They received 30 minutes of neuro- developmental therapy and clam exercise for 15 minutes, five times a week for three weeks. Muscle strength and walking ability were measured before and after the training period. Muscle strength was measured by Hand held dynamometer.The feedback group showed a significant improvement in hip abductor muscle strength and hip extensor muscle strength of the affected side (p